Key words Vocabulary of culture and society - Raymond Williams (New York Oxford University Press, 2015)
Featuring a new original foreword, written by Colin MacCabe A collection of 176 short essays on key words in our society Demonstrates how various words have changed over time to take on new meanings, and how these changes reflect our shifting values and politics.
Keywords: English Language